2006
DOI: 10.1136/emj.2006.039339
|View full text |Cite
|
Sign up to set email alerts
|

Review of calls to NHS Direct related to attendance in the paediatric emergency department

Abstract: Objective: To examine the outcomes of calls to NHS Direct (NHS-D) in relation to attendance at the accident and emergency (A&E) department. Design: A prospective collection of data about consecutive calls to NHS-D North West Coast was matched with attendances at the A&E department over a period of 3 months. Setting: NHS-D Regional Trust and a large urban paediatric A&E department. Patients: Children and young adults aged ,16 years living in local postal code areas. Main outcome measures: To examine (1) whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 2 publications
1
25
2
Order By: Relevance
“…Similarly, there has been a reduction in the ability of ambulance services to meet the national target of responding to 75% of life-threatening (Red 1) calls within 8 minutes. Performance nationally reduced from 76 In 2012/13, the intense public scrutiny culminated in a Health Select Committee inquiry, 2 and this scrutiny has continued. The pressure of increasing demand has more recently been exacerbated by acute shortages of associated health-care professionals, particularly in emergency medicine, 3 primary care 4 and ambulance services.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there has been a reduction in the ability of ambulance services to meet the national target of responding to 75% of life-threatening (Red 1) calls within 8 minutes. Performance nationally reduced from 76 In 2012/13, the intense public scrutiny culminated in a Health Select Committee inquiry, 2 and this scrutiny has continued. The pressure of increasing demand has more recently been exacerbated by acute shortages of associated health-care professionals, particularly in emergency medicine, 3 primary care 4 and ambulance services.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…72 57 also reported on appropriateness and 11 of the studies identified here were included in the review by Blank et al 73,[75][76][77][80][81][82]84,88,90 This review identified that triage decisions rated as appropriate varied between 44% and 98%. However, many different definitions of appropriateness were used, which leads to difficulty when trying to compare results.…”
Section: Service Impactsmentioning
confidence: 99%
“…Primary care OR general practice OR GP (these to be nested within terms such as GP co-operative) 12-22 three were eligible for quality assessment. 12,19,20 Four of the eleven studies concluded that telephone triage exerted little effect on A&E attendance. 7,14,15,17 A Cochrane systematic review incorporating six studies of varying service configurations found no evidence of a significant reduction in A&E attendances, with one study (of nurse-led telephone triage) demonstrating an increase.…”
Section: Box 1 Search Strategymentioning
confidence: 99%
“…12,17 Variations in the observed effect of telephone triage on A&E attendance rates may be attributable to various factors, including differences in triage service design. Studies covered interventions ranging from national telephone triage lines (for example, NHS Direct in the UK) 16,17,20,21 to local advice lines 14 and telephone services embedded within GP cooperatives. 15 Several studies identified poor telephone triage design (for example, unclear clinical algorithms) as explanations for inappropriate A&E referral.…”
Section: Box 1 Search Strategymentioning
confidence: 99%
“…In response to the article by Stewart et al 1 on a review of calls to NHS Direct related to attendance in the paediatric emergency department, we think it would be helpful to set some of the findings in context.…”
mentioning
confidence: 99%